2017
DOI: 10.4103/ijpc.ijpc_65_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise on cancer-related fatiguecommentary

Abstract: Background:Fatigue is the most common side effect of cancer treatment with chemotherapy and/or radiation therapy, selected biologic response modifiers. The main purpose of this study is to evaluate the effects of aerobic exercise on cancer-related fatigue in patients of the solid tumor after chemotherapy and radiotherapy.Methods:After screening for cancer-related fatigue, 34 patients fulfilled the inclusive criteria and were assigned into two groups (n = 17 recruited in the intervention group and n = 17 in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
2
9
0
1
Order By: Relevance
“…Findings from most studies have reported that exercise is a solution to pain, fatigue, and physical and mental function [ 7 10 ]. There is further evidence concerning the benefits of aerobic exercise in the rehabilitation of patients following cancer treatments [ 11 ]. A recent meta-analysis summarized that cancer patients in the aerobic training group reduced cancer-related fatigue compared to patients who received routine care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from most studies have reported that exercise is a solution to pain, fatigue, and physical and mental function [ 7 10 ]. There is further evidence concerning the benefits of aerobic exercise in the rehabilitation of patients following cancer treatments [ 11 ]. A recent meta-analysis summarized that cancer patients in the aerobic training group reduced cancer-related fatigue compared to patients who received routine care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most considerable variations between the studies were the frequency and duration of the interventions. Based on previous findings, it was expected that a period of 6 weeks of aerobic exercise may show a greater improvement in CRF and sleep disturbances 95 . However, due to the heterogeneity of the intervention frequencies and duration periods of the selected studies it is difficult to compare them.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Mustian et al (2017) [ 24 ], for example, showed that there was no direct correlation between the type of training and effectiveness. In contrast, Hilfiker et al (2018) [ 56 ] and Patel and Bhise (2017) [ 57 ] reported that endurance training in particular is very effective in CRF therapy.…”
Section: Discussionmentioning
confidence: 99%